The global burden of transportation tailpipe emissions on air pollution-related mortality in 2010 and 2015. (6th September 2019) - Anenberg, Susan C; Miller, Joshua; Henze, Daven K; Minjares, Ray; Achakulwisut, Pattanun
Abstract: Emissions from the transportation sector are a major contributor to ambient air pollution, the leading environmental health risk factor globally. This study aims to quantify the contribution of tailpipe emissions from global transportation, disaggregated by four sub-sectors, to the global disease burden associated with ambient fine particulate matter (PM2.5 ) and ground-level ozone in 2010 and 2015. We use the GEOS-Chem global chemical transport model to simulate transportation-attributable PM2.5 and ozone concentrations, combined with epidemiological health impact assessment methods consistent with the Global Burden of Disease 2017 study to estimate the associated burden of disease. We estimate that emissions from the transportation sector were associated with 361 000 (95% CI, 258 000–462 000) PM2.5 and ozone deaths in 2010 and 385 000 (95% CI, 274 000–493 000) in 2015. These results translate into 11.7% of total global ambient PM2.5 and ozone deaths in 2010 and 11.4% in 2015. Together, PM2.5 and ozone concentrations from transportation tailpipe emissions resulted in an estimated 7.8 million years of life lost and approximately $1 trillion (2015 US$) in health damages globally in 2015. Among transportation sub-sectors, on-road diesels contributed most to the health burden from transportation tailpipe emissions in nearly all trade blocs, for both PM2.5 and ozone, though other sub-sectors also contributed substantially (particularly on-road non-diesel vehicles for ozone mortality, and shipping and non-road mobile sources for PM2.5 mortality). These results indicate that despite recent adoption of more stringent vehicle emission regulations in many countries, the transportation sector remains a major contributor to the air pollution disease burden globally. Future work may explore the degree to which currently adopted policies, as well as expected growth in the transportation sector in India, Africa, and other rapidly developing locations, will influence future transportation-attributable public health burdens.